Orientifold Calabi-Yau threefolds with divisor involutions and string landscape - Altman, Ross; Carifio, Jonathan; Gao, Xin; Nelson, Brent D. (Journal of high energy physics, 2022)
We establish an orientifold Calabi-Yau threefold database for h1,1(X) ≤ 6 by considering non-trivial ℤ2 divisor exchange involutions, using a toric Calabi-Yau database (www.rossealtman.com/tcy). We first determine the topology for each individual divisor (Hodge diamond), then identify and classify the proper involutions which are globally consistent across all disjoint phases of the Kähler cone for each unique geometry. Each of the proper involutions will result in an orientifold Calabi-Yau manifold. Then we clarify all possible fixed loci under the proper involution, thereby determining the locations of different types of O-planes. It is shown that under the proper involutions, one typically ends up with a system of O3/O7-planes, and most of these will further admit naive Type IIB string vacua. The geometries with freely acting involutions are also determined. We further determine the splitting of the Hodge numbers into odd/even parity in the orbifold limit. The final result is a class of orientifold Calabi-Yau threefolds with non-trivial odd class cohomology ($$ {h}_{-}^{1,1} $$(X/σ*) ≠ 0).
Gesehen am 12.05.2022